KARAKTERISASI RESERVOAR BATU PASIR DENGAN MENGGUNAKAN TEKNIK INVERSI SEISMIK DAN ATRIBUT ATENUASI PADA DAERAH X - RANO
Sand reservoir UTAF-1 and LTAF-1 are located at X area. Characteristic and reservoir distribution of both target zones are different although they are located closely. In this research we have carried out lateral distribution estimation of sand reservoir for both layer mentioned. Data for analysis are 3D seismic data (Xline 95-710, inline 175-750) and 3 vertical well. By analyze crossplot between P-Impedance and Gamma ray which can differentiate sand from shale for both target, we can apply seismic inversion method to see lateral distribution of sand reservoir from both layer mentioned. Result shows by applying seismic inversion method which can differentiate sand from shale at UTAF-1 and LTAF-1 layer, so that sand both of layer can be mapped. The layers measure up to different: UTAF-1 layer character of reservoir high impedance, while LTAF-1 layer character of reservoir low impedance. While method of attenuation attribute fail to better to map the gas reservoir which possible because of some factor, for example enabled by because reservoir represent the flimsy layer and method estimate this Q its very sensitive to data quality.